Indonesians in Saudi Arabia: Worhsip and Work - Laurence Husson (Studia Islamika, 1997)
This article, which  opens a new  line of research,  is intended  to make a first assessment of the consequences  of Indonesian migration to saudi Arabia,  in particular  during  the  first half of the 2Oth century-a period when the immigration is bound  up with the pilgrimage from which Saudi Arabia draws a large part of its revenues. It must be added  that while documentary  evidence and partial studies on  this period  exist,  it turns out that documentation on the contemporary period  is scarce. This article also  is concerned with describing the evolution  of certain striking  aspects of the close  relation  between  the pilgrimage to Mecca  and Indonesian migrants  looking  for work.  We need to consider  the methods  of hiring  labor,  the networks  involved  in recruiting it, the organization  of travel,  as well as the increasing indebtedness  of the migrants  through  intermediaries  who, more and more professionally, arrange  these attempts  to live abroad, prompted in many cases by the same desire  for wealth.DOI: 10.15408/sdi.v4i4.767